Biosynthesis of ZnO Nanoparticles Mediated by Crescentia cujete L Leaves Extract and The Photocatalytic Activities Towards Methylene Blue - Demi Dama Yanti; Sintia Aprilia; Bambang Ariwahjoedi; Muhamad Allan Serunting; Hawa Purnama Celala Ary Cane (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
ZnO nanoparticles were synthesized using the precipitation method and using water extract of Crescentia cujete L leaves as a capping agent. ZnO nanoparticles with a hexagonal wurtzite structure were successfully synthesized with low production cost and environmentally friendly. According to XRD characterization, there is no impurity peak, indicating the ZnO nanoparticles have high purity and crystallinity. SEM images show the morphology of ZnO nanoparticles with semi-spherical shapes and an average size of 32.49 nm. The photocatalytic activity of ZnO nanoparticles was evaluated using a UV A lamp as a source of photonic energy toward methylene blue dye. Various irradiation times were carried out from 0, 10, 20, 30, 40, to 50 minutes, and a UV spectrophotometer was used to detect the concentration of methylene blue remains in collected samples. Increasing the irradiation times leads to increasing the photocatalytic activity of ZnO nanoparticles. At 50 minutes of exposure to a UV A lamp, the degradation percentage of methylene blue dye is 36.37%.